1986
DOI: 10.1128/mcb.6.6.1998
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of the Chinese hamster thymidine kinase gene.

Abstract: My colleagues and I have cloned a nearly full-length Chinese hamster thymidine kinase (TK) cDNA in a AgtlO vector and characterized this cDNA by nucleotide sequencing. The hamster TK protein is encoded in this cDNA by a 702-base-pair open reading frame which specifies a 25,625-dalton protein closely homologous to the previously described human and chicken TK proteins. Using cDNA nucleotide sequence data in conjunction with sequence data derived from selected subelones of the hamster TK gene recombinant phage X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
1

Year Published

1987
1987
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 81 publications
(44 reference statements)
2
20
1
Order By: Relevance
“…Moreover, recently it has been shown by means of sitedirected mutagenesis that the five highly conserved amino acids GXXGXGKT (where X represents various amino acids), which occur at residues 56 to 63 of the HSV-1 TK polypeptide, are essential for enzyme function and appear to be involved in the substrate-binding domains of the enzyme (Liu & Summers, 1988). The regions II and IV have a high degree of conservation among different herpesvirus TKs but similar sequences were not seen in poxvirus or mammalian TKs or adenylate kinases (Boyle et al, 1987 ;Bradshaw & Deininger, 1984;Kwoh & Engler, 1984;Lewis, 1986;Lin et al, 1985;Kuby et al, 1984). The functional roles of these two regions and of regions 'a' and 'b' of the polypeptide are still unknown.…”
Section: Tk Neutralization By Anti-tk Serummentioning
confidence: 99%
“…Moreover, recently it has been shown by means of sitedirected mutagenesis that the five highly conserved amino acids GXXGXGKT (where X represents various amino acids), which occur at residues 56 to 63 of the HSV-1 TK polypeptide, are essential for enzyme function and appear to be involved in the substrate-binding domains of the enzyme (Liu & Summers, 1988). The regions II and IV have a high degree of conservation among different herpesvirus TKs but similar sequences were not seen in poxvirus or mammalian TKs or adenylate kinases (Boyle et al, 1987 ;Bradshaw & Deininger, 1984;Kwoh & Engler, 1984;Lewis, 1986;Lin et al, 1985;Kuby et al, 1984). The functional roles of these two regions and of regions 'a' and 'b' of the polypeptide are still unknown.…”
Section: Tk Neutralization By Anti-tk Serummentioning
confidence: 99%
“…Most eucaryotic genes contain IVSs or introns that are excised from nuclear premRNA by the RNA splicing machinery (1,25,27,32). To gain insight into the nature of the putative high-molecularweight TK pre-mRNAs present in G,/S-and S-phase nuclei, as well as to determine whether there is a preferential order of IVS removal from the TK gene, we further characterized the TK pre-mRNA splicing intermediates present in S-phase cells by Northern (RNA) blot analysis.Mammalian TK genes, which contain seven coding exons and six introns, have been well conserved during evolution (6,20,23,31). We isolated unique sequence DNA probes from each of the six TK introns and used them to character-* Corresponding author.…”
mentioning
confidence: 99%
“…Mammalian TK genes, which contain seven coding exons and six introns, have been well conserved during evolution (6,20,23,31). We isolated unique sequence DNA probes from each of the six TK introns and used them to character-* Corresponding author.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that passage through a splicing pathway might be a general requirement for formation of stable cytoplasmic mRNA. Such a requirement could explain the poor transformation efficiency of various intronless minigenes (5, 16,17). However, rigorous reaffirmation of the importance of introns to eucaryotic mRNA formation has not been reported.…”
mentioning
confidence: 99%